Shalish and role of BRAC federation - Alim, Md. Abdul; Rafi, Mohammad (BRAC Research and Evaluation Division (RED), 2020)
The study aims to investigate the relationship between the federation and village shalish. Data were collected through qualitative method from federation members and the village heads participated in shalish. Members were found successful in playing their role in shalish. Inspiration and supports from some heads, spontaneous participation of other members, and the presidents being a member of union parishad contributed to succeed in shalish. Meanwhile, members became unsuccessful in shalish because of reverence of heads, uninterested male members, impediment of family members, unwillingness of sharing the incident among the members, hush money taken by the heads. Moreover, the informal and peculiar social, economic and political bondage between heads and federation members hampered to get the real justice. Few heads considered the federation as benevolent organization for the poor, as it might bring some societal changes in informal justice system in the village whereas others believed that it could not reach its goal because of the anecdotal values and culture of the villagers. Some members were ambitious about their success while others thought that they were poor, they had to spend most of their time to earn their livelihood, so how they could partake in shalish. However, the difficulties faced by the federation would continue yet they would be successful if they had been duly supported by BRAC.